Lesson Study in Teaching Young Learners: Assisting a Dynamic Classroom Interaction - Masyhud, Masyhud (English Education: Jurnal Tadris Bahasa Inggris, 2018)
This research aimed to administer the teacher students to improve their English teaching especially in assisting dynamic classroom interaction to young learners. The analysis of the research was descriptive based on Lesson Study (LS) as one of the teacher professional developments. It leads teacher students develop their professionalism collaboratively. The instruments of this research were documentation, observation, and field notes. The data were taken from cycles in Lesson Study (Plan, Do, and See). There were ten research participants with different roles; five students as observers and the other were the model teachers. Therefore, this LS applied five cycles. However, the result of this research revealed that LS facilitated teacher students to enhance their teaching. It was showed from the fifth cycles with five different teacher models where the classroom interaction was dynamically performed.